Avaliação do extrato de Cereus jamacaru como agente coagulante auxiliar ao sulfato de alumínio - Lacerda, Vinícius Fröner (2021)
The great need for quality water, whether for drinking water or industrial processes, is an obvious problem that afflicts the daily lives of public agents and water treatment and supply units. Water conservation is a necessity for all of humanity, considering its low availability, be it geographic or by quality. Due to the increase in consumption and the generation of effluents (water with waste), the need for methods and technologies to clean and improve this resource is clear. Water quality is a legal guarantee based on studies, norms and laws, and therefore strict quality standards that must be met by the water and effluent treatment units are established. The most simplified treatments are pre-treatment and primary treatment, which comprise a stage of elimination of coarse solids through grating and particulates and dissolved solids through coagulation. In general, the coagulation process eliminates the turbidity and color of the water, for this to occur, coagulating agents are used. Commercially, aluminum sulphate is the most widely used coagulating agent, since it has high availability and a more accessible value compared to others. However, the use of clotting agents despite eliminating a major problem can bring problems due to the release of ions that are often carcinogenic. This work proposed the use of a biocoagulant associated with aluminum sulfate as a form of treatment. Many biocoagulants are polymeric extracts from cacti, widely found in nature and easy to grow in different Brazilian biomes. The biocoagulant formulation by acid, basic and saline extract of the cactus popularly known as Mandacaru (Cereus jamacaru) and its influence on the physicochemical characteristics of the treatment and treatment efficiency was evaluated. It was found that the use of Mandacaru polymer showed an improvement in the coagulation process, an increase in the efficiency of turbidity reduction was verified when compared to the use without the organic polymer, and the basic extract polymer showed the best turbidity reduction.